Library Network Support Services: Modernising Libraries In Armenia, Moldova And Belarus Through Library Staff Development And Reforming Libraries [LNSS] : Prospect (Confluenţe Bibliologice, 2018)
The guide includes the objectives, purpose, achievements, impact and sustainability of the LNSS Project (15.10.2015 - 14.10.2018) within the ERASMUS+ Capacity Building Program in the field of higher education.
Keywords: LNSS project